Oncocytic Carcinoma of Parotid Gland: A Case Report - Nico Lumintang; Sherly Tandililing; Calenthia Ekawati (Universitas Sam Ratulangi, 2023)
Oncocytic carcinoma is a rare malignant carcinoma, representing only 5% of all oncocytic tumors. Furthermore, oncocytic carcinoma of the parotid gland is uncommon, accounting only for under 1% of all salivary gland tumors. We reported an 82-year-old female presented with a right parotid mass. She had experienced a similar complaint six months ago and had undergone treatment. Physical examination showed a mobile and painless cystic mass of the right parotid without facial nerve involvement. Fine needle aspiration biopsy (FNAB) finding suggested benign cystic lesions with inflammatory cells and amorphous debris. Subsequently, she underwent surgical tumor excision and right-sided partial parotidectomy. Histopathological examination showed proliferative tumor cells with an atypical nucleus, abundant eosinophilic cytoplasm, and solid, trabecular, and tubular growth pattern, suggesting an oncocytic carcinoma of the parotid gland. In conclusion, oncocytic carcinoma must be considered in all parotid gland tumors with oncocytic cells despite the rarity. Considering its recurrence and metastasis nature, patients with oncocytic carcinoma should remain in a long-term follow-up. The role of radiotherapy and chemotherapy remains controversial but may be used for treating advanced-stage cases or distant metastasis Keywords: oncocytic carcinoma; parotid gland; partial parotidectomy